Left ventricular remodeling in patients with rheumatoid arthritis and arterial hypertension - T. Yu. Kasimova; E. V. Arshin; A. V. Tuev; A. S. Rozenberg (Российский кардиологический журнал)
Aim. To study heart remodeling in patients with rheumatoid arthritis (RA) and/or arterial hypertension (AH); to identify clinical features of each remodeling type in individuals with RA and AH. Material and methods. In total, 257 patients were examined: 112 with RA and AH, 105 – with RA only, and 40 – with AH only. Heart structure and function was assessed by ultrasound method (“Acuson Aspen”, USA). Results. Pathological left ventricular (LV) remodeling types were observed in 97,5 %, 87 %, and 96,4 % of patients with AH only, RA only, and RA combined with AH, respectively. Concentric LV hypertrophy was typical for AH subjects (85 %). In RA subjects, all three LV remodeling types were observed: eccentric hypertrophy (22,3 %), concentric hypertrophy (27,2 %), concentric remodeling (36,9 %), together with normal heart geometry (13 %). In participants with AH and RA, LV remodeling types were similar to those in participants with isolated AH. Conclusion. In patients with AH and RA, eccentric LV remodeling was typically associated with early manifested RA, while concentric LV hypertrophy development was mostly determined by AH clinical course.